Measurement of cross sections for the reactions Cu-65(N,Alpha)Co-62g, Cu-65(N,P)Ni-65, Cu-65(N,2n)Cu-64, Ni-58(N,2n)Ni-57 And Ni-58(N,P)Co58m+G At 14.8 MeV neutron energy - Hafiz, M.A.; Rahman, M.M.; Harun-Ar-Rashid, A.K.M.; Khandaker, Mayeen Uddin; Islam, M.N.; Meazel, A.; Latif, S.A.; Halim, M.A.; Naher, K.; Chowdhury, M.N.; Uddin, M.S. (Springer Verlag (Germany), 2006)
An accurate knowledge of the activation cross section is important for several applications, especially in neutron (reactor) dosimetry and for the design of future reactors. So the investigation of the interaction of fast neutrons with the potential structural materials of nuclear reactors are very important for variety of specific purposes in the development and application of fission and fusion reactor technology. Cross sections were measured for (CU)-C-65(n,alpha)Co-62m, Cu-65(n,p)Ni-65, Cu-65(n,2n)Cu-64, Ni-58(n,2n)Ni-57 and Ni-58(n,p)Co58m+g reactions at the neutron energy 14.8 MeV by activation technique in combination with high resolution HPGe detector gamma-ray spectrometry. The results were compared with earlier reported experimental and theoretical values.